Perancangan Desain Logo Prima Mushroom dalam Rangka Membangun Identitas dan Strategi Branding Usaha - Astika Ulfah Izzati; Rini Rini; Silvana Oktanisa; Frianka Anindea; Welan Mauli Angguna; Septini Kumalaputri; Claudya Nurcahaya; Fernando Africano (Jurnal Pengabdian Masyarakat - PIMAS, 2023)
One of ways that can be done by Small and Medium Enterprise (SME) to improve their branding is by creating a logo. Logos can identify what products or services are produced by the enterprise, logos also differentiate one company from another, as well as one product from another. The business partner in this community service is Prima Mushroom which is owned by Ms. Teti Indrawati, located in Palembang City, South Sumatra Province. Initially the business partners had not built a good business identity where the partners already had a business name, but there was no logo that became the identity of this business. In addition, at the partner's business location there is no banner informing the name of the business. So this product is difficult to recognize by consumers. Therefore, the purpose of this community service activity is to design Prima Mushroom logo design and apply this logo to the business name information banner as a business branding strategy. The method used is to first socialize and discuss with partners regarding the problems faced, then solve the problems by providing alternative logo designs for business branding strategies.